A study of the optical properties of photopolymer Fabry-Perot microcavities by a dual-wavelength fibre optic architecture - Heredero, Raquel L (2019)
We present a novel method to study the behaviour of the optical properties of photopolymer materials with temperature. The photopolymer is deposited on the tip of optical fibres by dip coating to fabricate low-finesse Fabry–Perot microcavities. The signal processing technique utilized to interrogate the cavity is based on the generation of two quadrature phase-shifted interferometric signals using two Bragg fibre gratings. This technique enables the determination of the values of the thermo-optical coefficient and the linear coefficient of thermal expansion of the photopolymer. The effectiveness of the processing technique is also exploited in the study of the dependence of the temperature sensitivity on the cavity thickness.